Spatial energy transfer with observation of bimolecular singlet oxygen emission using quantum dots as donors and zinc‐phthalocyanine as acceptors. (8th January 2020) - Monte, Adamo F. G.; Azevedo, Guilherme; Reis, Arnaldo F.
Abstract: This study reports the influence of CdSe–ZnS core–shell quantum dots (QDs) for formation of singlet oxygen using zinc‐phthalocyanine (ZnPc) dyes in colloidal solutions. Using a microluminescence surface scan technique it was possible to measure accurately the photon diffusion length, or photon mean free path, inside the medium. Analyses were performed for a range of QD concentrations. Photon diffusion length was assigned to the bimolecular singlet oxygen emission at 707 nm. Related singlet oxygen emission was predicted by observing quenching of the photon diffusion length measured at the specific oxygen emission as a function of QD concentration, being a nontrivial phenomenon related to the QD donors. Diffusion length measured at 707 nm increased with QD concentration; in the absence of QDs, as in pure ZnPc samples, the emission peak at 707 nm was not observed.